A Burial Mound with Culture Layers from the Early Bronze Age near Torslev, Northern Jutland - Johansen, Erik (Journal of Danish Archaeology, 1985)
A Burial Mound with Culture Layers from the Early Bronze Age near Torslev, Northern Jutland